2019
DOI: 10.1080/1463922x.2018.1547458
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive and affective aspects on usability

Abstract: a industrial engineering, institut Teknologi sepuluh nopember, surabaya, indonesia; b industrial engineering, universitas Diponegoro, semarang, indonesia; c industrial engineering, university of surabaya, surabaya, indonesia ABSTRACT Studies on customer's needs, desires and preferences have become highly important in the product design and development process. One consideration in usability is the cognitive aspect, which is related to the accommodation and evaluation of human cognitive capabilities, limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Convenience sampling was used. Adopting the previous A-C-U framework [3], there were 3 hypotheses: H1: Cognition has positive impact on Affect at the e-commerce website transaction H2: Affect has positive impact on Usability at the e-commerce website transaction H3: Cognition has positive impact on Usability at the e-commerce website transaction…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Convenience sampling was used. Adopting the previous A-C-U framework [3], there were 3 hypotheses: H1: Cognition has positive impact on Affect at the e-commerce website transaction H2: Affect has positive impact on Usability at the e-commerce website transaction H3: Cognition has positive impact on Usability at the e-commerce website transaction…”
Section: Methodsmentioning
confidence: 99%
“…E-commerce website is a vital feature of online business information platforms, and it is full of complex customer mental process experience. Study by Prastawa et al [3] shows that cognition is still found to be the primary determinant of usability. Once it is replicated to other product experience or service settings, the results could be different.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Such indicators consist of pleasure in interacting with the site, pleasantness to look at, preferred features, and positive feelings for the site. The perceived usability factor is measured by four indicators, namely comfort when used, ease when used, easy orientation, and easy navigation (Prastawa et al 2019). Based on the researches by Al-Shamaileh (2013) and Hinderks et al (2019), classical aesthetics refers to traditional aesthetic ideas that emphasize orderly and clear design.…”
Section: User Experience (Ux)mentioning
confidence: 99%
“…The affective dimension plays a crucial role in the usability criterion, although satisfaction as an integral aspect of that criterion has received little attention. It has been proposed in the Information Systems (IS) area that the emotive elements of a design, such as colors, images, and shapes, in􀅫luence the overall perception of the Information System (Mazhar & Anwar, 2012;Prastawa, Ciptomulyono, Laksono-Singgih, & Hartono, 2019). Users like to use and return to well-structured websites where they can readily discover the information they need, according to (Martinez et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%